ARTISTIC LANGUAGE AND ECOLINGUISTICS (On the example of Otkir Hashimovʼs novel “Dreams of Past Lives”) (Scientific journal of the Fergana State University, 2024)
In this article, the emerging modern directions emerging modern trends in linguistics and the fact that ecolinguistics is one of the current trends of Uzbek linguistics and the preservation of language purity, which is one of the problems of linguistics, are described. The author dwells on some ecolinguistic phenomena in Otkir Hashimov’s novel “Dreams of Past Lives”.